Synthesis of uniformly distributed optimal control with nonlinear optimization of oscillatory processes - Kerimbekov, A.; Asanova, Zh.K.; Baetov, A.K. (Bulletin of the Karaganda University. Mathematics Series, 2024)
In the article the problem of synthesizing uniformly distributed optimal control for nonlinear optimization of oscillatory processes described by integro-differential partial differential equations with the Volterra integral operator was explored. The study was conducted according to the Bellman-Egorov scheme and an algorithm for constructing a uniformly distributed optimal control in the form of a functional from the state of the controlled process was developed. Sufficient conditions for the solvability of the synthesis problem in nonlinear optimization were established.